PENERAPAN LESSON STUDY BERBASIS PROJECT BASED LEARNING (PJBL) PADA PEMBELAJARAN MATEMATIKA KELAS II SDN 02 RAKAM - Istifirrah Rabiatul Mawaddah; Burhanuddin; Husnul Fajri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of Lesson Study based on the Project-Based Learning (PjBL) model in mathematics learning for second-grade students at SDN 02 Rakam. The study employed a quantitative descriptive method involving 23 second-grade students in the second semester of the 2025/2026 academic year. The research was conducted through the sequential stages of Plan, Do, and See. Data were collected through classroom observations, learning achievement tests, and documentation. The data were analyzed using descriptive statistics, including percentages of lesson implementation, teacher and student activities, classical learning mastery, and classical learning absorption. The findings indicated that the implementation of Lesson Study based on Project-Based Learning was carried out very effectively. The developed learning instruments were categorized as very good based on validation results and classroom implementation observations. Teacher and student activities during the learning process also achieved a very good category, as reflected in the increased student participation, collaboration, and engagement in completing project-based learning activities. The evaluation results showed that the students achieved an average score of 89.74, with the highest score of 95 and the lowest score of 85. Keywords: Lesson Study, Project-Based Learning, Mathematics, Learning Outcomes, Elementary School.